Avaliação da exposição ao mercúrio e seus compostos sobre o desenvolvimento neuropsicomotor em crianças de Porto Velho-RO - MARQUES, Rejane Corrêa (Universidade Federal do Pará, 2013)
A cohort of 100 births was generated during november and december of 2000 in Porto Velho city. Mothers and her newborns had been examined to verify total mercury levels (TML) at the birth, and the course of posnatal exposure on development and growth of infants during the first semester of their extrauterine life. To evaluation of prenatal exposure TML at the birth in samples of maternal and newborns hair, placenta, umbilical coord, and maternal blood had been analyzed. The newborns underwent physical and clinical examination. Mothers answered a questionnare that included important infonnations about risk factors to mercury accumulation or that could affect the development and growth of her childrens. At six months of age, 86 of the infants underwent detailed phisical and neurobehavioral examination, to evaluate the postnatal exposure. Besides a new sample of infants hair had been analyzed to verify TML. All data had been analyzed, compared, and underwent statistical evaluation. 23 infants (26%) showed neurological developmental disturbance at six months of age. This had been correlated with TML in children hair as at birth as at 6 months of age. A statistically significant correlation was observed between the head circumference and TML' s in the several analyzed samples.